2022
DOI: 10.3390/jcm11102842
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Assessment and Management in Patients with Cirrhosis and Cognitive Impairment: A Comprehensive Review of Literature

Abstract: Hepatic encephalopathy (HE) represents a common complication of liver cirrhosis. Protein-calorie malnutrition is frequently encountered in the cirrhotic patient and its most obvious clinical manifestation is sarcopenia. This condition represents a risk factor for HE occurrence because skeletal muscle acts as an alternative site for ammonium detoxification. Preventive intervention through an adequate assessment of nutritional status should be carried out at early stages of the disease and in a multidisciplinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…According to Johnson et al, anti-health eating habits hinder the process of treatment. The lack of observance of diet and malnutrition of patients with cirrhosis of the liver significantly deteriorate the clinical status of this organ [29]. It was observed that patients who were ordered a special diet after the diagnosis of hepatitis C, to a higher degree expected emotional support (7.23 scores), compared to those who did not receive dietary recommendations (6.39 scores; p>0.05).…”
Section: Discussionmentioning
confidence: 99%
“…According to Johnson et al, anti-health eating habits hinder the process of treatment. The lack of observance of diet and malnutrition of patients with cirrhosis of the liver significantly deteriorate the clinical status of this organ [29]. It was observed that patients who were ordered a special diet after the diagnosis of hepatitis C, to a higher degree expected emotional support (7.23 scores), compared to those who did not receive dietary recommendations (6.39 scores; p>0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Since malnutrition worsens the prognosis, in addition to the treatment of the underlying causes of cirrhosis and its complications when they occur, an early assessment of nutritional status should be performed in these patients [64]. Nowadays, both instrumental and non-instrumental tools are available to asses nutritional status in cirrhotic patients, such as the bioimpedance test, handgrip strength, DEXA and computed tomography scans for the first category, and food diaries, objective examinations, biochemical parameters (level of total plasma protein), anthropometric measurements, the creatine-to-weight ratio and subjective global assessment questionnaires in the latter category [65]. As well as nutritional assessments, dietary control is a valid tool to improve nutritional status and prognosis.…”
Section: Muscle Alterationsmentioning
confidence: 99%
“…There is no evidence suggesting that restricting dietary protein prevents episodes of HE. The daily calorie requirement falls within the range of 35 to 45 kcal/gm, while the protein requirement is recommended to be 1.2 to 1.5 gm/kg of body weight per day 26,27 .…”
Section: Nutritionmentioning
confidence: 99%